Influence of alkylaromatic hydrocarbons on the efficiency of linear alkylbenzene sulfonic acid synthesis; Chemical Engineering Journal; Vol. 329 : XXII International conference on Chemical Reactors CHEMREACTOR-22, 1 December 2017 - Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Dolganova I. O. Irena Olegovna; Frantsina E. V. Evgeniya Vladimirovna; Dolganov I. M. Igor Mikhailovich (2017, 2017)
Title screen